Kerangka Konsep Keluarga Malaysia dalam Mencapai Kesejahteraan - Abdul Rashid Abdul Aziz; Muhammad Khairi Mahyuddin; Muhammad NubliAbdul Wahab; Husin Sungkar; Nurun Najihah Musa; Nur A'in Mustafar (Secholian Publication, 2024)
Indexed by MyCite